2009
DOI: 10.1159/000262608
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Serum Prolidase Activity and Increased Oxidative Stress in Early Pregnancy Loss

Abstract: Aims: To compare the levels of serum prolidase activity and oxidative stress markers including total oxidative status (TOS), total antioxidant capacity (TAC), lipid hydroperoxide (LOOH) and total free sulfhydryl (–SH) in healthy pregnant women without early pregnancy loss (EPL) and women with EPL. Methods: Serum samples were obtained from 45 healthy first-trimester pregnancies and 45 pregnancies complicated with EPL. We have measured serum prolidase activity, TAC, TOS, –SH and LOOH levels spectrophotometricall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 58 publications
0
19
0
1
Order By: Relevance
“…Its levels were also shown to negatively correlate with increased OS, possibly accounting for the heightened placental vascular resistance and endothelial dysfunction secondary to decreased and dysregulated collagen turnover [156]. …”
Section: Pregnancy Complicationsmentioning
confidence: 99%
“…Its levels were also shown to negatively correlate with increased OS, possibly accounting for the heightened placental vascular resistance and endothelial dysfunction secondary to decreased and dysregulated collagen turnover [156]. …”
Section: Pregnancy Complicationsmentioning
confidence: 99%
“…Prolidase activity is related to the pathogenesis of various diseases Savas et al 2010;Sezen et al 2010;Toy et al 2009aToy et al , 2010Vural et al 2010b;Yildiz et al 2008a). Since its property of representation of collagen turnover, prolidase is an important marker for tumour size and aggression of the fi broid growth (Wolanska et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…However, on the basis of some of the past studies, a direct effect of vitamin E on the erythroid cells for induction of Hb appears plausible. For example, in mouse model, vitamin E Infertility duration (in years) 5.69±2.71 6 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11) All the values quoted as the mean±SD and median (min-max). Unpaired t-test was used to compare the results between two groups.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] One study of 45 women that had experienced recurrent pregnancy loss found significantly decreased total antioxidant capacity (TAC) and increased total oxidative National Journal of Physiology, Pharmacy and Pharmacologystatus among these women compared to healthy pregnant controls. [7] α-tocopherol is the chemical name for the most active form of vitamin E. Vitamin E (α-tocopherol) is an exogenous, lipid soluble potent antioxidant molecule. [8] It is thought to be a direct free radical scavenger by activating the intracellular antioxidant enzymes and saving the cell membranes from lipid peroxidation.…”
Section: Introductionmentioning
confidence: 99%